Little rot - Emezi, Akwaeke (Riverhead Books, 2024)
"Aima and Kalu are a long-time couple who have just split. When Kalu, reeling from his loss, visits a sex party hosted by his best friend Ahmed, he makes a decision that will plunge them all into chaos, brutally upending their lives. Ola and Souraya, two Nigerian sex workers visiting from Kuala Lumpur, intersect with the three old friends as everything goes to hell. Sucked into the city's corrupt underworld, they're all looking for a way out of the trouble they've instigated, driven by loss and fueled by a desperate need to escape the dangerous threat that looms over them. They careen madly in the face of the poison of power, sexual violence, murder, betrayals. Little Rot tests how far these five will go to save each other--or themselves--when confronted by evil, culminating in a shattering denouement."--